2019
DOI: 10.1093/brain/awz204
|View full text |Cite
|
Sign up to set email alerts
|

The functional neuroanatomy of emotion processing in frontotemporal dementias

Abstract: Impaired processing of emotional signals is a core feature of frontotemporal dementia syndromes, but the underlying neural mechanisms have proved challenging to characterize and measure. Progress in this field may depend on detecting functional changes in the working brain, and disentangling components of emotion processing that include sensory decoding, emotion categorization and emotional contagion. We addressed this using functional MRI of naturalistic, dynamic facial emotion processing with concurrent indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 72 publications
2
35
0
Order By: Relevance
“…Several studies have reported relationships between the Rolandic operculum and psychology (or emotion) with or without an external factor (disease) and/or intervention (substance abuse). The role of the operculum is also related to emotion processing through music 15 , 16 and facial expression 17 . Mean diffusivity of the Rolandic operculum is positively correlated with indices of empathizing-cooperativeness 18 and depressive symptoms 19 , and hypoactivation in the right parietal and central operculum is associated with impaired emotion processing due to alcohol dependence 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported relationships between the Rolandic operculum and psychology (or emotion) with or without an external factor (disease) and/or intervention (substance abuse). The role of the operculum is also related to emotion processing through music 15 , 16 and facial expression 17 . Mean diffusivity of the Rolandic operculum is positively correlated with indices of empathizing-cooperativeness 18 and depressive symptoms 19 , and hypoactivation in the right parietal and central operculum is associated with impaired emotion processing due to alcohol dependence 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The SVM classi er showed that the abnormalities in brain memory networks had a high power to discriminate SCD from CN on an individual subject basis, with an ACC of 86.0%, an AUC of 92.9%, 83.8% sensitivity, and 89.1% speci city, which suggests that this study identi es a HIPsub pathological circuit related to SCD. The HIPe network connectivity in SCD subjects is predominantly abnormal in the brain regions involved in many aspects of emotional processing, including the cerebellum [39,40], anterior insula [39,41], parahippocampa gyrus [39,42], and fusiform gyrus [43]. Indeed, SCD subjects are characterized by self-reported concerns regarding their memory decline [44], which signi cantly increases the risk of AD [5].…”
Section: Discussionmentioning
confidence: 99%
“…The SVM classi er showed that the abnormalities in brain memory networks had a high power to discriminate SCD from CN on an individual subject basis, with an ACC of 86.0%, an AUC of 92.9%, 83.8% sensitivity, and 89.1% speci city, which suggests that this study identi es a HIPsub pathological circuit related to SCD. The HIPe network connectivity in SCD subjects is predominantly abnormal in the brain regions involved in many aspects of emotional processing, including the cerebellum [21,22], anterior insula [21,23], parahippocampa gyrus [21,24], and fusiform gyrus [25]. Indeed, SCD subjects are characterized by self-reported concerns regarding their memory decline [26], which signi cantly increases the risk of AD [5].…”
Section: Discussionmentioning
confidence: 99%